Decreased Level of Vitamin D is Associated with Rheumatoid Arthritis Patients from Western Region of Nepal - Karki, D; Nagila, A (Journal of Gandaki Medical College-Nepal, 2018)
Background: Rheumatoid Arthritis (RA) is a progressive, chronic type of autoimmune disease and the role of vitamin D in the pathogenesis of RA is under investigation. Objective: The objective of this study was to determine the vitamin D deficiency in patients with RA as compared to healthy controls and to assess the relationship between serum vitamin D and anti-cyclic citrullinated peptide (anti-CCP) antibody levels in patients with newly diagnosed rheumatoid arthritis. Methods: The study was conducted between January 2017 to February 2018 at Fishtail Hospital and Research centre. A total of 63 patients with early RA diagnosed and a control group of 56 healthy participants, not on vitamin D supplements were recruited from Department of Internal Medicine. Five ml of blood samples were drawn from cubital veins. Blood glucose, creatinine, uric acid, calcium, RA factor, 25-hydroxy vitamin D, anti-CCP antibody, and erythrocyte sedimentation rates were measured in a centralized laboratory of Fishtail Hospital and Research centre. Results: The level of serum 25-hydroxy vitamin D were significantly lower in RA group (20.03 ±9.97 ng/mL) in comparison to the control group (24.46 ±8.45 ng/mL) (p<0.003). Our result indicates the prevalence of vitamin D deficiency was more in RA group compared with control group (47.61% vs. 33.16%, p <0.002). The level of Anti-CCP is significantly high in RA group than control group. In RA patients serum 25-hydroxy vitamin D levels were negatively correlated to anti-CCP antibody levels (rs = 0.72, p <0.001), and erythrocyte sedimentation rate (rs = 3.95, p <0.005). Conclusion: In RA patient vitamin D deficiency is quite common and serum 25-hydroxy vitamin D level was negatively correlated to anti-CCP antibody level. Our results suggest that vitamin D level is a motivation factor rather than a consequence of RA activity.